2022
DOI: 10.1021/acsmacrolett.2c00683
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Dependence in Photoiniferter Polymerization

Abstract: We report on a fundamental feature of photoiniferter polymerizations mediated with trithiocarbonates and xanthates. The polymerizations were found to be highly dependent on the activated electronic excitation of the iniferter. Enhanced rates of polymerization and greater control over molecular weights were observed for trithiocarbonate-and xanthate-mediated photoiniferter polymerizations when the n → π* transition of the iniferter was targeted compared to the polymerizations activating the π → π* transition. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…The disparities in the rates of photoiniferter polymerization were attributed to the higher rate of C–S photolysis. This explanation was validated through model trapping studies …”
Section: Chemical Mechanisms Used In Raft-mediated 3d Printingmentioning
confidence: 89%
See 1 more Smart Citation
“…The disparities in the rates of photoiniferter polymerization were attributed to the higher rate of C–S photolysis. This explanation was validated through model trapping studies …”
Section: Chemical Mechanisms Used In Raft-mediated 3d Printingmentioning
confidence: 89%
“…This explanation was validated through model trapping studies. 56 In a highly efficient photoiniferter RAFT process, degenerative chain transfer is identified as the primary source of control over polymerization. Nevertheless, there is a need for additional experimental and theoretical research to fully understand the extent of the mechanism of reversible deactivation.…”
Section: D Printing Via Photoinifertermentioning
confidence: 99%
“…Very recently, Sumerlin and coworkers reported that irradiation with visible light to target n → π* electronic transitions led to more efficient and well-controlled polymerization than irradiation with UV light to target π → π* electronic transitions, if the light intensity was identical (0.6 mW cm −2 ). 407 Due to the spin-forbidden nature, n → π* electronic transitions show a much smaller molar extinction coefficient than π → π* electronic transitions. Nevertheless, the polymerization results and the radical-trapping experiment using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) confirmed that n → π* electronic transitions led to the higher quantum yield of photolysis of the C–S bond, higher radical concentration, and more rapid polymerization.…”
Section: Photoiniferter Polymerizationmentioning
confidence: 99%
“…The monomer scope was expanded to methacrylates, 110,157,280,381,399,400 acrylates, 33,88,110,134,157,[401][402][403][404][405][406][407][408] acrylamides, 33,110,157,404,407,409 AN, 410 2-vinylpyridine (2-VP), 411 styrene, 404,406 and fluoro(meth)acrylates 412 (Table 4). Compared to UV light, the use of milder visible light (460 nm, 4.8 W) prohibited the self-initiation of MA although the induction period was increased by four times.…”
mentioning
confidence: 99%
“…This phenomenon has been demonstrated for other types of photopolymerization in literature as well. [ 89 ]…”
Section: Photochemistry Of Pvksmentioning
confidence: 99%